A fine line between red and dark: Anti-communist film-induced tourism - Handayani, Bintang; Costa, Jean Henrique (Turyzm/Tourism, 2021)
This study explores the ‘30 September Movement’ that staged a communist coup in 1965 as travel motivation for an anti-communism museum. ‘Framing’ and ‘uses and gratifications’ theories were used for this case study. The findings concluded that negative film plots and scenes are signature themes that can be used as attributes of red or dark film motivations for tourism. The use of theories, such as ‘framing’ and ‘uses and gratifications’, along with reflexive thematic analysis has provided unique and valuable theoretical insights that may be overlooked by other analyses.